Where Code Comes From: Architectures of Automatic Control from Babbage to Algol. - Haigh, Thomas; Priestley, Mark (Communications of the ACM, 2016)
The article discusses the history of automatic control and computer programs. Details on the automatic computer known as the Analytical Engine, developed by scientists Charles Babbage and Ada Lovelace, and on automatic digital computers such as the Mark I computer developed by IBM, are presented. Other topics include the ENIAC and EDVAC computers and the use of loops and branches in computer programming.